2018
DOI: 10.1038/s41598-018-22819-3
|View full text |Cite|
|
Sign up to set email alerts
|

Loss of the adaptor protein ShcA in endothelial cells protects against monocyte macrophage adhesion, LDL-oxydation, and atherosclerotic lesion formation

Abstract: ShcA is an adaptor protein that binds to the cytoplasmic tail of receptor tyrosine kinases and of the Low Density Lipoprotein-related receptor 1 (LRP1), a trans-membrane receptor that protects against atherosclerosis. Here, we examined the role of endothelial ShcA in atherosclerotic lesion formation. We found that atherosclerosis progression was markedly attenuated in mice deleted for ShcA in endothelial cells, that macrophage content was reduced at the sites of lesions, and that adhesion molecules such as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Expressions of both ICAM-1 and VCAM-1 are produced on endothelial cells of atherosclerotic plaque development by several mediators, including ROS and ox-LDL 55 . More importantly, ICAM-1 and VCAM-1, expressed by abnormal endothelium in developing atherosclerotic plaques, are required for the circulating monocyte recruitment to atherosclerotic lesions 56 . Moreover, VCAM-1 has been shown to play a dominant role in the initiation of atherosclerosis 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Expressions of both ICAM-1 and VCAM-1 are produced on endothelial cells of atherosclerotic plaque development by several mediators, including ROS and ox-LDL 55 . More importantly, ICAM-1 and VCAM-1, expressed by abnormal endothelium in developing atherosclerotic plaques, are required for the circulating monocyte recruitment to atherosclerotic lesions 56 . Moreover, VCAM-1 has been shown to play a dominant role in the initiation of atherosclerosis 57 .…”
Section: Discussionmentioning
confidence: 99%
“…These target genes of ZEB1 are involved in the modulation of angiogenesis, endothelial dysfunction, monocyte‐endothelial cell interactions, macrophage lipid accumulation, macrophage polarization, monocyte‐VSMC interactions, VSMC proliferation and migration, and T cell proliferation (Table 1). Although most studies have demonstrated the beneficial effects, a recent research showed a paradoxical result that ZEB1 can positively regulate intercellular adhesion molecule‐1 (ICAM‐1) expression, promoting the monocyte‐macrophage adhesion and atherosclerotic lesion formation (Abou‐Jaoude et al, 2018). The association between ZEB1 and atherosclerosis appears complicated.…”
Section: Discussionmentioning
confidence: 99%
“…Cell fractionation -Cells were seeded in P100 dishes and, 24 hours after seeding, were transfected with either scrambled siRNA, or siRNA against p66, p52 and p46 isoforms of ShcA (Dharmacon) at a final concentration of 100 nM using lipofectamine 3000 (Thermo Fischer Scientific). 48 hours posttransfection, the cells were fractionated as previously described (22). Confocal Microscopy -Primary chondrocytes were seeded on glass slides, and 48 hours later were fixed with 3% paraformaldehyde, and incubated with anti-RunX2 (Cell signaling Technology), anti-YAP1 (Cell signaling Technology), anti-IgG control primary antibodies and Alexa Fluor 488 (Fischer Scientific) secondary antibodies.…”
Section: Methodsmentioning
confidence: 99%